2022
DOI: 10.1038/s41598-022-16215-1
|View full text |Cite
|
Sign up to set email alerts
|

IHACRES, GR4J and MISD-based multi conceptual-machine learning approach for rainfall-runoff modeling

Abstract: As a complex hydrological problem, rainfall-runoff (RR) modeling is of importance in runoff studies, water supply, irrigation issues, and environmental management. Among the variety of approaches for RR modeling, conceptual approaches use physical concepts and are appropriate methods for representation of the physics of the problem while may fail in competition with their advanced alternatives. Contrarily, machine learning approaches for RR modeling provide high computation ability however, they are based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The Multilayer Perceptron (MLP) is a widely used artificial neural network consisting of multiple interconnected layers of neurons. It includes input, output, and hidden layers and is trained using backpropagation [ 6 ]. The input layer receives signals, the output layer performs tasks such as prediction [ 38 ], and the hidden layers serve as the primary computational engine for the MLP [ 39 ].…”
Section: Multilayer Perceptron Optimized By Particle Swarm Optimizati...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Multilayer Perceptron (MLP) is a widely used artificial neural network consisting of multiple interconnected layers of neurons. It includes input, output, and hidden layers and is trained using backpropagation [ 6 ]. The input layer receives signals, the output layer performs tasks such as prediction [ 38 ], and the hidden layers serve as the primary computational engine for the MLP [ 39 ].…”
Section: Multilayer Perceptron Optimized By Particle Swarm Optimizati...mentioning
confidence: 99%
“…R –R models can be categorized differently based on their spatial and structural processing methods, including physical, empirical, conceptual, distributed, lumped, and semi-distributed models. Each category possesses distinct advantages and drawbacks [ [6] , [7] , [8] , [9] ]. Moreover, climate change has complicated the rainfall-runoff relationship even further, leading to more nonlinear and intricate processes along with increased frequencies and severity of floods and droughts.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, machine learning (ML) systems for drought forecasting have attracted considerable interest [14,15]. In addition, several types of research have shown that AI algorithms outperform conventional approaches [16][17][18][19], such as artificial neural network (ANN) [20], support vector machines (SVMs) [21], random forests [22], and the adaptive neuro-fuzzy inference system (ANFIS) [23], which are examples of these ML systems. In recent decades, different developed types of ML approaches have been widely used for drought modeling tasks; for example, Inoubli et al [24] investigated the ability of the LSTM model for SPEI forecasting in East Azerbaijan province in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these modern data-driven approaches are showing promising results, they are only slowly tested on catchments in Switzerland. For instance, Mohammadi et al (2022) recently combined the outputs of three existing conceptual models used in Switzerland with a MLP neural network to estimate the river runoff in the Emme watershed in central Switzerland. Also, only a handful of studies have focused on leveraging the predictive power of neural networks for application in glacier-influenced catchments.…”
Section: Introductionmentioning
confidence: 99%